Impact of the time of surgical delay on survival in patients with muscle-invasive bladder cancer - Li, Shuaishuai; Chen, Rui; Raj, Ashok; Xue, Ning; Zhao, Fangzheng; Shen, Xihao; Peng, Yunpeng; Zhu, Haitao (Frontiers in Oncology, 2022)
Abstract Background and Objectives: Patients with muscle-invasive bladder cancer (MIBC) often experience a waiting period before radical surgery for numerous reasons; however, the COVID-19 outbreak has exacerbated this problem. Therefore, it is necessary to discuss the impact of the unavoidable time of surgical delay on the outcome of patients with MIBC. Methods: In all, 165 patients from high-volume centers with pT2-pT3 MIBC, who underwent radical surgery between January 2008 and November 2020, were retrospectively evaluated. Patients’ demographic and pathological information was recorded. Based on the time of surgical delay endured, patients were divided into three groups: long waiting time (> 90 days), intermediate waiting time (30–90 days), and short waiting time (≤ 30 days). Finally, each group’s pathological characteristics and survival rates were compared. Results: The median time of surgical delay for all patients was 33 days (interquartile range, IQR: 16–67 days). Among the 165 patients, 32 (19.4%) were classified into the long waiting time group, 55 (33.3%) into the intermediate waiting time group, and 78 (47.3%) into the short waiting time group. The median follow-up period for all patients was 48 months (IQR: 23–84 months). The median times of surgical delay in the long, intermediate, and short waiting time groups were 188 days (IQR: 98–367 days), 39 days (IQR: 35–65 days), and 16 days (IQR: 12–22 days), respectively. The 5-year overall survival (OS) rate for all patients was 58.4%, and that in the long, intermediate, and short waiting time groups were 35.7%, 61.3%, and 64.1%, respectively (P = 0.035). The 5-year cancer-specific survival (CSS) rates in the long, intermediate, and short waiting time groups were 38.9%, 61.5%, and 65.0%, respectively (P = 0.042). The multivariate Cox regression analysis identified age, time of surgical delay, pT stage, and lymph node involvement as independent determinants of OS and CSS. Conclusion: In patients with pT2-pT3 MIBC, the time of surgical delay > 90 days can have a negative impact on survival.